National memory in cinema... How do historical films reflect the momentous events in Algerian society? The film "Opium and the Stick" as a case study - NAOUI, Kamel; LADJAL, Taher; SETTATHA, Chaima; AMEUR, Hamadi (Journal of Ecohumanism, 2026)
The study aims to introduce Algerian cinema through the film Opium and the Stick, and to reveal the oppressive methods adopted by French colonialism against the Algerian people during the liberation revolution, while highlighting the role of image and sound in conveying the message of the Algerian revolution to the world and strengthening national memory. The researcher relied on the descriptive approach through descriptionThe events covered in the film and the analysis of their conformity with the historical facts of the Algerian liberation revolution. The study sample was represented in the Algerian historical film Opium and the Stick by director Ahmed Rachidi, as a model for studying the representations of national memory in Algerian cinema. The study relied on analyzing the content of the film and comparing its events with the historical facts and the original novel by Mouloud Mammeri, i.e. through observation and documentary analysis of the cinematic text. Perhaps the most important results: It is the contribution of the film Opium and the Stick in embodying the Algerian national memory and highlighting the sacrifices of the people during the liberation revolution. The film highlighted the pivotal role of the Algerian countryside in supporting the revolution humanly and logistically, and revealed practices.Oppressive French colonialism, such as scorched earth politics and mass revenge, and as this study has proven, Algerian cinema is an effective tool in preserving collective memory, transmitting it to future generations, and strengthening national identity.